2008
DOI: 10.1017/s1074070800002340
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Credit Risk in Agriculture: Implications for Capital Structure Analysis

Abstract: Signaling is an important element in the lender-borrower relationship that influences the cost and availability of debt capital to agricultural borrowers. This paper analyzes the effects of signaling on farm capital structure in conjunction with the pecking order and trade-off theories. The aggregate estimation indicates that signaling does affect agricultural credit relationships through measures of past cash flow and profitability. High-quality borrowers achieve greater credit capacity by providing lenders w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
0
25
0
8
Order By: Relevance
“…Zhao et al . () analysed the financial effects of signalling on farm's credit capacity and investment conditions for crop farms in Illinois. Their results indicated that signalling affects agricultural credit relationships between lenders and borrowers.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al . () analysed the financial effects of signalling on farm's credit capacity and investment conditions for crop farms in Illinois. Their results indicated that signalling affects agricultural credit relationships between lenders and borrowers.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (e.g. [7], [8], [14] and others) have verified their new proposed risk evaluation model on a sample of data of farms. These studies therefore also included the practical application of the proposed risk evaluation models.…”
Section: Resultsmentioning
confidence: 98%
“…Internal equity and debt are the major financing alternatives, while external equity and direct access to capital markets are beyond the reach of most farms. Nonetheless, capital intensity of farm businesses is high, production cycles can be lengthy and seasonal, life cycle effects are present, and rates of return on assets are relatively low and volatile (Zhao et al, 2008 Ratio analysis is often used as a tool of financial analysis within the agricultural sector (Katchova and Enlow, 2013). If we compare results from the previous two tables (microaspect: analysis of business success), we can see that the agricultural companies of Serbia have even 10 times higher share of financing responsibilities compared to Slovenia (growth of indebtedness), whereas they have even 3 times lower coefficient of stock turnover (poor sales and cash management).…”
Section: Results -Part Ii: Comparative Analysismentioning
confidence: 99%